Hemophagocytic lymphohistiocytosis presenting as acute coronary syndrome - Gabriel Melki; Mina Fransawy Alkomos; Sushant Nanavati; Vinod Kumar; Christina Mariyam; Michael Maroules (University of São Paulo, 2021)
Acquired Hemophagocytic Lymphohistiocytosis is a rare and deadly syndrome resulting from an overactive immune system, with uncontrolled activation of macrophages and lymphocytes, hypercytokinemia, and systemic inflammatory response. A 75-year-old male presented with typical anginal pain and was diagnosed with the acute coronary syndrome, which required a percutaneous transluminal coronary angioplasty. Instead of resolving the symptoms, the patient began to exhibit pyrexia and worsening altered sensorium with progressing renal failure, anemia, thrombocytopenia and respiratory failure. This constellation of symptoms caused the patient to require mechanical ventilation and hemodialysis. Upon laboratory analysis, hyperferritinemia provided an indication to the diagnosis of acquired hemophagocytic lymphohistiocytosis. After the initiation of dexamethasone, the patient made a significant recovery and was discharged from the hospital.